Protecting livelihoods? : a study of informal traders at Mitchell's Plain town centre market - Huss, Mary Laura (Department of Social Development, 2015)
The implementation of a new citywide Informal Trading By-law and a permit system for registering traders left over 200 traders without a space to trade. Using multiple qualitative research methods, document review, interviews, photography and observation, this study seeks to highlight the experiences and views of a group of MPTCM traders working to protect their livelihoods.